The EPICAL trial, a phase Ib study combining first line afatinib with anti-EGF vaccination in EGFR-mutant metastatic NSCLC. (February 2022) - Rodríguez-Abreu, D.; Cobo, M.; García-Román, S.; Viteri-Ramírez, S.; Jordana-Ariza, N.; García-Peláez, B.; Reguart, N.; Aguilar, A.; Codony-Servat, J.; Drozdowskyj, A.; Molina-Vila, M.A.; d'Hondt, E.; et al.
Highlights: Combination of anti-EGFR monoclonal antibodies or immune checkpoint inhibitors with TKIs has shown minimal benefit in EGFR mutant ( EGFR -mut) NSCLC patients. Consequently, new combination approaches are needed. EPICAL was a single arm, phase 1b study to evaluate safety, tolerability and anti-tumor activity of first line afatinib combined with anti-EGF vaccination in advanced EGFR -mut patients. Combination treatment with an anti–EGF vaccine is well tolerated, induces a sustained immunogenic effect and might enhance the clinical efficacy of EGFR TKIs. Abstract: Introduction: Combination of anti-EGFR monoclonal antibodies or immune checkpoint inhibitors with TKIs has shown minimal benefit in EGFR mutant ( EGFR -mut) NSCLC patients. Consequently, new combination approaches are needed. Patients and methods: The EPICAL was a single arm, phase 1b study to evaluate safety, tolerability and anti-tumor activity of first line afatinib combined with anti-EGF vaccination in advanced EGFR -mut patients. EGFR status and mutations in liquid biopsies were determined by reverse transcriptase-polymerase chain reaction; serum biomarkers by ELISA and Western blotting analysis. Results: The assay enrolled 23 patients, 21 completed the anti-EGF immunization phase. Treatment was well tolerated and no serious adverse events (SAEs) related to the anti-EGF vaccine were reported. Objective response and disease control rates were 78.3% (95%CI = 53.6–92.5) and 95.7% (95%CI = 78.1–99.9), respectively. After a median follow-up of 24.2 months, median progression-free survival (PFS) was 14.8 months (95% CI = 9.5–20.1) and median overall survival (OS) 26.9 months (95% CI = 23.0–30.8). Among the 21 patients completing the immunization phase, PFS was 17.5 months (95% CI = 12.0–23.0) and OS 26.9 months (95% CI = 24.6-NR). At the end of the immunization phase, all 21 patients showed high serum titers of anti-EGF antibodies, while EGF levels had decreased significantly. Finally, treatment with fully immunized patient's sera inhibited the EGFR pathway in tumor cells growing in vitro . Conclusions: Combination treatment with an anti–EGF vaccine is well tolerated; induces a sustained immunogenic effect and might enhance the clinical efficacy of EGFR TKIs.